2019
DOI: 10.3892/mco.2019.1951
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of small‑sized peripheral squamous cell lung cancer

Abstract: Recent advances in imaging technology have enhanced the detection rate of small-sized peripheral lung cancers. The present study aimed to identify the clinicopathological differences between patients with small-sized peripheral squamous cell carcinoma (SCC) and adenocarcinoma (ADC). Patients with lung cancer who underwent radical surgical resection at Gunma University Hospital between July 2007 and October 2012 were retrospectively analyzed. Patients who exhibited small-sized peripheral tumors (pathological si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…However, the eighth edition of the TNM classification does not distinguish between histologic types for the pathologic stage of NSCLC 26 . In addition, lung adenocarcinoma without GGO has a similar prognosis to squamous cell carcinoma 6,11 . In this study, the histologic type was not a significant prognostic factor in the multivariate analysis that compared the effect of LGC and histologic type on the prognosis of NSCLC, suggesting that the difference in prognosis between adenocarcinoma without an LGC and NSCLC can be attributed to adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, the eighth edition of the TNM classification does not distinguish between histologic types for the pathologic stage of NSCLC 26 . In addition, lung adenocarcinoma without GGO has a similar prognosis to squamous cell carcinoma 6,11 . In this study, the histologic type was not a significant prognostic factor in the multivariate analysis that compared the effect of LGC and histologic type on the prognosis of NSCLC, suggesting that the difference in prognosis between adenocarcinoma without an LGC and NSCLC can be attributed to adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 54%
“…One of the limitations of using adenocarcinoma for prognostication in previous studies is that the prognosis was thought to differ depending on the histologic type. Some studies have shown that adenocarcinomas have a better prognosis than squamous cell carcinomas 6,11,23 . In contrast, adenocarcinoma without a GGO component has an equivalent risk of postoperative recurrence compared with squamous cell carcinoma 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lymphatic invasion was not evaluated in this study, it has been reported that it is associated with high-grade patterns. 39,40 It is also important to note that the proposed grading system has not been validated in variants of adenocarcinoma, including invasive mucinous adenocarcinoma. Further studies are necessary to evaluate the applicability and performance of the model in these special tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The main prognosis elements for stage I NSCLC, as reported in previous studies, included age, sex, smoking status, visceral pleural invasion, type of resection, histology subtype, and differentiation. [4][5][6] And there is no consensus on whether postoperative adjuvant therapy is beneficial for stage I NSCLC.…”
Section: Introductionmentioning
confidence: 99%